Islamic Certificate of Bank Indonesia (SBIS)'s Impact on Indonesian Economic Growth - Safitri, Alisya Esa; Sekaringsih, Riswanti Budi (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2022)
This study aims to determine the effect of monetary policy indicators, particularly Islamic Certificates of Bank Indonesia (SBIS), on economic growth in Indonesia. The dependent variable in this study is economic growth seen from the value of GDP. The independent variables used in this study are the money supply, BI rate, inflation, exchange rate (exchange rate), and Islamic Certificates of Bank Indonesia (SBIS). The type of data used in this study is secondary data in monthly time series (time series) from January 2010 to December 2019 sourced from the Central Statistics Agency (BPS) and Bank Indonesia (BI). This study uses the Vector Error Correction Model (VECM) analysis method. The VECM estimation results show that the effect of the money supply, BI rate, and Islamic Certificates of Bank Indonesia (SBIS) on economic growth in Indonesia in the short term is positive, but in the long term, it has a negative effect. Inflation in the short and long term does not affect economic growth in Indonesia. The exchange rate in the short term does not affect economic growth in Indonesia, while in the long term, it has a positive effect.Keywords: Economic Growth, Money Supply, BI Rate, SBIS, VECM.